Ways of Knowing and Caring Used by Nurses in Community Hospice Agencies. Issue 1 (February 2018) - Ferguson, Rita
Abstract : Providing nursing care for an individual who is terminally ill is a complex endeavor. Understanding the different ways nurses who work in hospice agencies use knowing about and caring for persons receiving services becomes important because the actions of nurses are influenced by the nurses' perceptions. Hearing the narrative of nurses providing end-of-life care through phenomenological research can inform nursing education and institutions' methods to support the development of skills and characteristics to improve palliative and end-of-life nursing care. The purpose of this research was to question nurses who work in hospice agencies concerning their lived experiences related to knowing about and caring for individuals who were receiving hospice services. Four themes were identified related to the concepts of knowing and caring. These are difficult-to-measure concepts but add value to the profession and document how nurses contribute to patient care. In addition, the concepts are meaningful to patients and families receiving hospice services. The research provided a method of making the work of these nurses visible and gave more knowledge about nurses who provide end-of-life care.